Travels of Ibn Battuta : a guided Arabic reader - Dimeo, David (The American University in Cairo Press, 2016)
"While telling a fascinating narrative as a whole, each of the twenty lessons is designed to stand alone for classroom or individual study. Individual sections focus on classical grammar and stylistics, historical and cultural background and critical evaluation of the texts. The book also provides teachers with a wide range of comprehension, composition, interpretation, and research activities."--P. [4] of cover.